Inconsistent Provider Testing Practices for Congenital Cytomegalovirus: Missed Diagnoses and Missed Opportunities - Kate L. Wilson; Kimi Shah; Megan H. Pesch (MDPI AG, 2022)
Newborn congenital cytomegalovirus (cCMV) screening programs have been found to increase the rates of early diagnosis and treatment. In North America, newborn cCMV screening programs have not been widely implemented, leaving healthcare providers to rely on clinical suspicion alone to prompt testing. This study sought to examine healthcare providers' cCMV testing practices at a quaternary children's hospital. A retrospective review of the electronic health record was completed for eligible infants over a six-year period. Bivariate calculations and analyses were performed. Between 2014 and 2019, a total of 40,091 infants were cared for at the study institution, of which 178 were tested for cCMV and 10 infants were diagnosed with cCMV. Isolated small-for-gestational age was the most common indication (53/178) to prompt testing. Overall, the cCMV testing rate was 4.5 tests per 1000 infants, with a resulting diagnostic prevalence of 0.2 cases per 1000 infants, which is 15-fold lower than the expected prevalence. Providers relying on clinical suspicion alone are infrequently testing infants for cCMV, resulting in missed diagnoses and missed opportunities for treatment. Systematic cCMV screening practices may improve diagnosis, treatment, and childhood outcomes.